Wood-Cement Boards (WCB) from Bambusa Vulgaris / Jamaludin Kasim, Chen Fung Woo and Rahim Sudin - Kasim, Jamaludin; Chen, Fung Woo; Sudin, Rahim (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
Bambusa vulgaris taken from the riverside of Sg. Benus, Bentong, Pahang was found to be suitable in the manufacture of (WCB). It contains a high amount of sugars and was found to have a retarding effect on cement setting. In the study, higher cement ratio gives better board properties. Board with a bamboocement ratio of 1:2.75 with the addition of 2% chemical additives produces an acceptable board which meets the requirements of the Malaysian Standard MS934.